Public health awareness and seroprevalence of rabies in dogs in Limpopo National Park, and the phylogeny of rabies virus in Mozambique - Fafetine, Jose Manuel (University of Pretoria, 2023)
Thesis (PhD (Veterinary Tropical Diseases))--University of Pretoria, 2021.